2005
DOI: 10.1177/0021998305048733
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Damage in Composite Cylinders After Impact

Abstract: This paper presents the results from a study in two parts. The first part involves the identification and modeling of damage initiation and development in glass-reinforced epoxy composite cylinders subjected to drop weight impact. The second is concerned with the evaluation of the influence of this damage on the residual strength under hydrostatic pressure loading. Original results showing the influence of damage on implosion pressure are presented. The improved understanding of these phenomena and the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…In addition, the pipe specimen impacted with the energy level of 5 J consistently showed higher burst pressure than those impacted with energy levels of 7.5 J and 10 J. The same reduction in burst strength on impacted pipes were also reported by some authors [17][18][19]22,24]. Fig.…”
Section: Burst Strengthsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, the pipe specimen impacted with the energy level of 5 J consistently showed higher burst pressure than those impacted with energy levels of 7.5 J and 10 J. The same reduction in burst strength on impacted pipes were also reported by some authors [17][18][19]22,24]. Fig.…”
Section: Burst Strengthsupporting
confidence: 81%
“…In the monotonic burst tests, three damage modes were observed: whitening, weepage and eruption [24]. The whitening stage was observed in the filament winding direction during early monotonic burst test, indicating the progressive evolution of damage in the matrix cracks and debonding of the fibre-matrix [18]. The weepage failure was observed on the specimen surface impacted by the low energy level (5 J).…”
Section: Burst Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the damage produced by low energy impact leads to a reduction of the implosion pressure. Tarfaoui et al [11][12][13][14] carried out an extensive test program, arriving at the same conclusion that the impact damage reduces considerably the implosion pressure. Moreover, the same author [15] was able to predict the impact curves with good accuracy, using finite element model with progressive failure analysis (based on Hashin failure criterion [16]).…”
Section: Introductionmentioning
confidence: 91%
“…This provides the structural designer with a wide range choice of mechanical properties. Properly designed filament winding composite cylinders are widely used for pressure vessels and main sections of hollow-slender shaped aerospace structures with the main advantage of lightweight over their metallic counterparts [3,4]. Being composed of hoop and helical layers which with the characteristic of unidirectional ply, matrix crack-induced leakage may occur at a stress level much lower than the ultimate strength of fiber in filament wound composite pressure vessel applications.…”
Section: Introductionmentioning
confidence: 99%